Simulation of 6 pulse GTO thyristor converter and harmonics analysis - Nurul Diyana, Mohamed (2009)
This project is about the simulation of 6 pulse GTO thyristor converter circuit and their harmonics analysis when the LC filter circuit is added to the system. Gate turn-off thyristor (GTO) are four-layer PNPN devices that act as switches, rectifiers, and voltage regulators. It is a fully controllable switches which can be turned on and off by their third lead, the GATE lead. Besides that, it is also high-power semiconductor device which make it suitable to be used in High-voltage Direct Current (HVDC) systems. The 6 pulse converter is also known as 3 phase fully controlled Full Wave Bridge Converter and can be functioned as a rectifier or an inverter. This project used OrCAD PSpice simulator to simulate the results for the analysis purpose. Computer simulation is a very economical and time effective approach to design the circuit since it is an attempt to model a real-life or hypothetical situation on a computer so that it can be studied to see how the system works and if the simulation is successful, further action can be taken to prepare the hardware. It is also can be used in large scale system such as HVDC. The GTO thyristor model must be create since it is not included in the library of OrCAD PSpice. Using the GTO thyristor model, the 6 pulse GTO thyristor converter circuit will be created in OrCAD PSpice simulator. The evaluation and analysis of performance of simulation studies for a 6 pulse converter using PSPICE simulators with GTO thyristor as a control element is continue by adding the LC filter circuit to improve the performance of the converter circuit by reducing the harmful effects of the harmonics current. The harmonic for the circuit before and after adding the LC filter circuit is analyse and compared. The simulation results of DC output voltage is also will be compared to the mathematical calculation results by using graph. This contribution can be very useful particularly for the operation and maintenance personnel who can perform better with greater insight into the functioning of the complex system obtained through the model as developed.